2021
DOI: 10.3389/fphar.2021.664465
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Breakfast Increases Bioavailability of Albendazole Compared to Low-Fat Breakfast: Single-Dose Study in Healthy Subjects

Abstract: Purpose: Albendazole is a benzimidazole carbamate drug with anthelmintic and antiprotozoal activity against intestinal and tissue parasites. It has been described that the administration with meals increases albendazole absorption. Our aim was to compare the systemic exposure in healthy volunteers of two albendazole formulations after a single oral dose under fed conditions and to evaluate the effect of breakfast composition on albendazole and albendazole sulfoxide bioavailability.Methods: 12 healthy volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…In-keeping with previous work [22,23,3234], consumption of a fatty meal prior to receiving the dose was associated with increased bioavailability of albendazole, increasing the amount absorbed into the body (and concomitantly elevating the AUC and C Max values achieved), a phenomenon thought to be attributed to changes in the drug’s solubility (previously shown to be the rate-limiting step in albendazole’s bioavailablity and absorption [27]) when delivered alongside a fatty meal [34]. Whilst prior results from the literature have suggested (modest) differences between men and women in albendazole’s pharmacokinetics (specifically with regards to the AUC and C Max [19]), we did not observe any statistically significant differences here.…”
Section: Discussionsupporting
confidence: 82%
“…In-keeping with previous work [22,23,3234], consumption of a fatty meal prior to receiving the dose was associated with increased bioavailability of albendazole, increasing the amount absorbed into the body (and concomitantly elevating the AUC and C Max values achieved), a phenomenon thought to be attributed to changes in the drug’s solubility (previously shown to be the rate-limiting step in albendazole’s bioavailablity and absorption [27]) when delivered alongside a fatty meal [34]. Whilst prior results from the literature have suggested (modest) differences between men and women in albendazole’s pharmacokinetics (specifically with regards to the AUC and C Max [19]), we did not observe any statistically significant differences here.…”
Section: Discussionsupporting
confidence: 82%
“…Menbutone would act in a similar way as a fatty meal in healthy human subjects. In this way, Ochoa et al ( 17 ) reported an increase in the oral bioavailability of albendazole due to a higher dissolution of this drug in the gastrointestinal tract by stimulating bile secretion.…”
Section: Discussionmentioning
confidence: 99%
“…MEN could participate in the mechanisms proposed. More recently, Ochoa et al [ 28 ] reported that a fatty meal enhances ABZ oral bioavailability in healthy human subjects, attributing this higher absorption to food-induced stimulation of bile secretion, increasing the drug solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the surfactant effect of the bile salts may be related to a higher dissolution of ABZ in the gastrointestinal tract and, consequently, to an increased absorption of this drug [ 27 , 28 , 29 ]. Solubility, but not absorption, was the rate limiting step in the bioavailability of this anthelmintic [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%